Case studies in post-prostatectomy complications - Bailly, Greg (Canadian Urological Association Journal, 2013)
As part of the program at the 3rd Annual Canadian Urology Forum (2013), participants engaged in interactive discussions of difficult cases throughout the event. The following is a summary of discussions pertaining to two challenging cases illustrating the management of complications, subsequent to radical prostatectomy.